(untitled) (Neo Scientific Peer Reviewed Journal, 2023)
In given article, the topical problems in the education of young people, such as self-knowledge, the formation of the phenomenon of human knowledge, the study of man as an external aesthetic, spiritual and aesthetic, moral and social value are considered.